Predicting Innovative Behavior Among Employees in a Manufacturing Company: The Role of Psychological Capital - Ika Zenita Ratnaningsih; Anggun Resdasari Prasetyo; Unika Prihatsanti (ANIMA Indonesian Psychological Journal, 2016)
The aim of this study is to investigate the relationship between psychological capital and workplace innovative behavior. The importance of innovative behavior in the competitive business world has been widely recognized. Previous studies have examined variables related to innovative behavior both at personal and organizational levels; however, there is a paucity of research looking at psychological capital as the predictor of workplace innovative behavior. In this study psychological capital and innovative behavior of 149 non-managerial employees in an apparel manufacture company were measured using Psychological Capital Scale (20 items, α = .872) and Innovative Behavior Scale (nine items, α = .874). The regression analysis shows a significant positive correlation between these two variables (r = .519, p < .01) and 27% of variance in innovative behavior can be explained from psychological capital. The results are discussed in relation to its theoretical contribution and practical implications in organizational contexts.